2019
DOI: 10.3389/fneur.2019.00867
|View full text |Cite
|
Sign up to set email alerts
|

History of Hypertension Is Associated With MR Hypoperfusion in Chinese Inpatients With DWI-Negative TIA

Abstract: Objectives: The present study aimed to examine the prevalence of and risk factors for magnetic resonance (MR) perfusion abnormality in a Chinese population with transient ischemic attack (TIA) and normal diffusion-weighted imaging (DWI) findings. Methods: Patients with TIA admitted to our stroke center between January 2015 and October 2017 were recruited to the present study. MRI, including both DWI and perfusion-weighted imaging (PWI), was performed within 7 days of symptom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…They also observed a strong correlation between hypertension and perfusion abnormalities that was independent of the ischemic attack (Wang et al, 2019b). Hypertension, together with hypoperfusion, can result in significant dysregulation of cerebral vessels, increasing vascular resistance and exacerbating myogenic constriction (Iddings et al, 2015).…”
Section: Hypoperfusion and Oxidative Stress In Hypertensionmentioning
confidence: 93%
See 1 more Smart Citation
“…They also observed a strong correlation between hypertension and perfusion abnormalities that was independent of the ischemic attack (Wang et al, 2019b). Hypertension, together with hypoperfusion, can result in significant dysregulation of cerebral vessels, increasing vascular resistance and exacerbating myogenic constriction (Iddings et al, 2015).…”
Section: Hypoperfusion and Oxidative Stress In Hypertensionmentioning
confidence: 93%
“…Using MRI analyses and clinical history data for 59 patients who suffered a transient ischemic attack, Wang and colleagues reported that 67.8% of such patients presented a history of hypertension. They also observed a strong correlation between hypertension and perfusion abnormalities that was independent of the ischemic attack ( Wang et al, 2019b ). Hypertension, together with hypoperfusion, can result in significant dysregulation of cerebral vessels, increasing vascular resistance and exacerbating myogenic constriction ( Iddings et al, 2015 ).…”
Section: Vascular Risk Factors and The Nvumentioning
confidence: 98%
“…MRI-based hypoperfusion in patients with TIA is closely related to the time of completing MR imaging. A recent study has shown that hypoperfusion, detected by MRI, is present in 42.4% (25/59) of patients with TIA, and the median (IQR) time of symptom onset to baseline MR-PWI was 5 (4–9) days (Wang et al, 2019a ). This is similar to the results of a previous study that has demonstrated the presence of hypoperfusion in 42% (57/137) of patients with TIA, with a median time of 9.2 h from symptom onset to completing MR-PWI (Asdaghi et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of the volume of hypoperfusion on MRI perfusion scans are performed using the RAPID software, which is an automated image post-processing software (Rothwell et al, 2007 ; Wang et al, 2019a ). Lesion volume of T max ≥ 4 s ≥ 10 ml is used for determining perfusion deficits in patients with TIA (Liu et al, 2007 ; Najib et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation